Evaluación del comportamiento de la variedad de Rosa Freestyle (Rosa Spp.) almacenada en seco: Cayambe-Ecuador 2011 - Pilicita Sánchez, María Cristina (2012)
This research was carried out in the flower "Pacific Sun" located in the community of Juan Montalvo, Cayambe Canton, Pichincha province, Ecuador. The aim was to evaluate the performance of the Freestyle variety of rose (Rosa spp) stored in dry, for it raised the following objectives: The design was a RCBD with a factorial arrangement AxBxC where the factors under study were hours of harvest (7:30 am and 11:00), breakpoints (Russian and American) and coverage of cases (with and without cover) a total of 8 treatments and 24 boxes or experimental units.